2019–2020 Florida Citrus Production Guide: Introduction - Lauren M. Diepenbrock; Megan M. Dewdney; Tripti Vashisth (EDIS)
This 3-page fact sheet is the introduction to the 2019–2020 Florida Citrus Production Guide. The goal of the Florida Citrus Production Guide is to serve as a reference for information needed to guide decision-making in Florida citrus-growing operations. Written by Lauren M. Diepenbrock, Megan M. Dewdney, and Tripti Vashisth, and published by the Plant Pathology Department, March 2019.